Thermophysical Properties of Silicon Dioxide (SiO2) in Ethylene Glycol/Water (EG/W) Mixture for Proton Exchange Membrane Fuel Cell Cooling Application - Talib, S. F. A.; Azmi, W. H.; Irnie, Zakaria; W. A. N. W., Mohamed; A. M. I., Mamat; H., Ismail; W. R. W., Daud (Elsevier Ltd, 2015)
Polymer Electrolyte Membrane Fuel Cells (PEMFC) operation is sensitive to micro electrochemical changes and can only tolerate a small temperature variation for optimal power generation. An effective cooling system is needed to comply with this condition. Nanofluids are perceived as a potential coolant for thermal management in PEMFC application that allows for more compact design. The dispersion of nanofluid in water-ethylene glycol base fluid enhances the thermal conductivity for improved heat transfer. The thermal conductivity, viscosity and electrical conductivity of different Silicon Dioxide (SiO2) concentrations diluted in Ethylene Glycol/Water (EG/W) mixtures of 40EG, 50EG and 60EG are reported. However, the electrical conductivity would contribute to electrical leakage and is a limiting factor for fuel cell operation. Highest value of thermal conductivity recorded is the dispersion of nanofluid in 40EG whereas the viscosity of SiO2 is the highest in 60EG dilution. Electrical conductivity is recorded the highest in EG/W 40:60% with 0.5% of SiO2. However, the electrical conductivity would contribute to electrical leakage and is a limiting factor for fuel cell operation.